Preclinical Evaluation of a B7-H3 Targeting Antibody Enhancing NK Cell-Mediated Cytotoxicity for Ovarian Cancer Treatment - Hagelstein I; Mattern S; Wang K; Haueisen YE; Greiner SM; Englisch A; Staebler A; Singer S; Lutz MS (ImmunoTargets and Therapy)
Ilona Hagelstein,1– 3 Sven Mattern,4 Kevin Wang,1– 3 Yannick E Haueisen,1– 3 Sarah M Greiner,1,2,5 Alexander Englisch,1,5,6 Annette Staebler,4 Stephan Singer,3,4 Martina S Lutz1– 3 1German Cancer Consortium (DKTK), Partner Site Tuebingen, a Partnership Between DKFZ and University Hospital Tuebingen, Tuebingen, Germany; 2Clinical Collaboration Unit Translational Immunology, Department of Internal Medicine, University Hospital Tübingen, Tuebingen, Germany; 3Cluster of Excellence iFIT (EXC 2180) Image-Guided and Functionally Instructed Tumor Therapies, University of Tuebingen, Tuebingen, Germany; 4Department of Pathology and Neuropathology, University Hospital Tuebingen, Tuebingen, Germany; 5Department of Obstetrics and Gynecology, University Hospital Tuebingen, Tuebingen, Germany; 6Department of Peptide-Based Immunotherapy, Institute of Immunology, University and University Hospital Tuebingen, Tuebingen, GermanyCorrespondence: Martina S Lutz, CCU Translational Immunology, Department of Internal Medicine, University Hospital Tuebingen, Otfried-Mueller-Str. 10, Tuebingen, 72076, Germany, Email martina.lutz@med.uni-tuebingen.deBackground: Despite the advancements in treatment, ovarian cancer remains the deadliest gynecological malignancy. The dismal prognosis of the disease necessitates the urgent development of novel therapies. Monoclonal antibodies (mAbs) have transformed cancer treatment, yet their effectiveness in ovarian cancer remains limited. A key mechanism in mAb therapy is antibody-dependent cellular cytotoxicity (ADCC), driven by natural killer (NK) cells targeting tumor cells. Optimization of the Fc domain of mAbs to enhance efficacy has therefore become a subject of extensive research. The costimulatory molecule B7-H3 is overexpressed in various cancers, including ovarian cancer, making it a promising target for anti-tumor mAb immunotherapy. This study evaluates the preclinical potential of an Fc-optimized B7-H3-targeting antibody for ovarian cancer treatment.Methods: The expression of B7-H3 was evaluated in tumor samples from 43 ovarian cancer patients using immunohistochemistry. A chimeric B7-H3 mAb was developed with a wildtype Fc (8H8-WT) and an Fc-optimized variant (8H8-SDIE) containing S239D/I332E substitutions to enhance CD16 binding and subsequent activation of NK cells. The therapeutic effects of 8H8-SDIE were evaluated through NK cell activation, cytokine release, and cytotoxicity assays.Results: A total of 43 ovarian cancer samples were analyzed, and it was found that all of them expressed B7-H3. In addition, 8H8-SDIE was found to demonstrate significantly higher affinity for CD16 than 8H8-WT, with minimal effects on other Fc receptors. Functional assays confirmed that 8H8-SDIE enhanced NK cell activation and promoted IFN-γ and TNF release. Furthermore, 8H8-SDIE induced robust cytotoxicity against B7-H3-expressing ovarian cancer cells in both short-term and long-term assays.Conclusion: 8H8-SDIE has been shown to induce potent NK cell activity, resulting in tumor cell lysis. This finding underscores its promise as an innovative immunotherapeutic approach for the treatment of ovarian cancer. Keywords: B7-H3, monoclonal antibody, ovarian cancer, NK cell, immunotherapy